2020
DOI: 10.1289/ehp6161
|View full text |Cite
|
Sign up to set email alerts
|

Residential Greenness and Cardiovascular Disease Incidence, Readmission, and Mortality

Abstract: BACKGROUND: Living in greener areas of cities was linked to increased physical activity levels, improved mental well-being, and lowered harmful environmental exposures, all of which may affect human health. However, whether living in greener areas may be associated with lower risk of cardiovascular disease incidence, progression, and premature mortality is unclear. OBJECTIVES: We conducted a cohort study to examine the associations between residential green spaces and the incidence of acute myocardial infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 54 publications
1
25
2
Order By: Relevance
“…More importantly, the results of our study exhibited a greater protective effect of greenness exposure on hypertension incidence than prior published literature included older adults [9,11,14,16], which indicated that the advantages of greenness for these oldest people were greater than expected. Our results provide new insights that the bene t of greenness exposure to hypertension prevention possible increases with age, especially for the oldest old people.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…More importantly, the results of our study exhibited a greater protective effect of greenness exposure on hypertension incidence than prior published literature included older adults [9,11,14,16], which indicated that the advantages of greenness for these oldest people were greater than expected. Our results provide new insights that the bene t of greenness exposure to hypertension prevention possible increases with age, especially for the oldest old people.…”
Section: Discussioncontrasting
confidence: 40%
“…Third, published studies reported there was a modi cation effect of the relationship between greenness and blood pressure varied by elderly's age. Some studies proposed this protective effects were stronger in younger age elderly but others were not, due to the rare sample for oldest-old people, this modi cation effect of age was not fully understand [9,10,14]. In addition, previous cross-sectional study designs have dominated the literature [7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement or construction of new environmental amenities such as parks, entwined with political and economic agendas, may ultimately socially and physically exclude or even displace long-term underprivileged residents, a process that has been called green or environmental gentrification [ 42 ]. Greenspace availability has been associated with a wide range of health outcomes [ 43 45 ]. Exposure to greenspaces alone has also been linked to decreased health inequalities [ 43 , 46 – 48 ].…”
Section: Future Directions—moving Beyond a Generalist’s Perspectivementioning
confidence: 99%
“…2 Many studies have associated green space with beneficial health effects, including enhanced restoration, improved perceived wellbeing and mental health, [3][4][5][6] and reduction in cardiovascular disease. 7,8 Additionally, green spaces are associated with decreased natural-cause mortality. 5,9 75% of the European population lives in urban environments.…”
Section: Introductionmentioning
confidence: 99%